Resting state connectivity in people living with HIV before and after stopping heavy drinking - Gullett, Joseph M.; DeFelice, Jason; Richards, Veronica L.; Porges, Eric C.; Cohen, Ronald A.; Govind, Varan; Salan, Teddy; Wang, Yan; Zhou, Zhi; Cook, Robert L. (Frontiers in Psychiatry, 2023)
Background: Heavy alcohol use in people living with HIV (PLWH) has widespread negative effects on neural functioning. It remains unclear whether experimentally-induced reduction in alcohol use could reverse these effects. We sought to determine the effects of 30-days drinking cessation/reduction on resting state functional connectivity in people with and without HIV. Methods: Thirty-five participants (48.6% PLWH) demonstrating heavy alcohol use attempted to stop drinking for thirty days via contingency management (CM). MRI was acquired at baseline and after thirty days, and functional connectivity across five resting-state fMRI (rsfMRI) networks was calculated with the Conn toolbox for Matlab and examined in relation to transdermal alcohol concentration (TAC) recorded by the ankle-worn secure continuous remote alcohol monitor (SCRAM) and self-reported alcohol use (timeline follow-back; TLFB). Associations between alcohol use and reduction, HIV status, functional connectivity, and change in functional connectivity across five major rsfMRI networks were determined relative to the pre- and post-CM timepoints. Results: Baseline resting-state functional connectivity was not significantly associated with average TAC-AUC during the pre-CM period, though higher self-reported alcohol use over the preceding 30 days was associated with higher baseline connectivity within the Dorsal Attention Network (p-FDR<0.05). Baseline salience network connectivity was negatively related to objective drinking reduction after intervention (p-FDR<0.05), whereas baseline limbic connectivity was positively associated with self-reported drinking reduction (p-FDR<.05). Change in between-networks connectivity after intervention was positively associated with biosensor-confirmed drinking reduction, where higher reduction was associated with stronger connectivity between the limbic and fronto-parietal control networks (p-FDR<0.05). Lastly, PLWH with lower DAN connectivity at baseline demonstrated poorer alcohol reduction than those with higher DAN connectivity at baseline. Discussion: Lower resting-state functional connectivity of the Salience network significantly predicted stronger drinking reduction across all participants, suggesting a potential biomarker for reduced susceptibility to the environmental and social cues that often make alcohol use reduction attempts unsuccessful. Increased between-networks connectivity was observed in participants with higher alcohol reduction after CM, suggesting a positive benefit to brain connectivity associated with reduced drinking. PLWH with lower baseline DAN connectivity may not benefit as greatly from CM for alcohol reduction.